IDENTIFIKASI KARAKTER MORFOLOGI DAN ANATOMI MANGGA LOKAL (Mangifera spp.) MOROWALI DI DESA BENTE DAN DESA BAHOMOLEO KECAMATAN BUNGKU TENGAH - Moh. Sadri; Enny Adelina; Sakka Samudin (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
This study aimed to assess the characteristics of mango plants based on their leaf morphology and anatomy in Bahomoleo and Bente villages, Central Bungku sub district, Morowali district. Observation on morphological features was implemented in Bahomoleo and Bente village, whereas anatomical observations were made in the Laboratory of Biotechnology, Faculty of  Mathematics and Natural Sciences of Tadulako University.  The study was conducted in March to May 2016. The morphological parameters observed included plant age, plant height, stem diameter, canopy diameter, canopy shape and bar color.  The leaf anatomy variables consisted of stomata size, epidermis size, stomata number, epidermis number, stomatal density and stomatal index.The morphological and anatomical characters observed based on a cluster analysis and were described in a dendogram form. The results of cluster analysis of both villages on the distance of 0.648 resulted in three accessions namely BT1, BT8 and BM9. The highest stomatal index of both villages is the accession BT8 and the lowest accession is the BM9, while the highest stomatal density/mm2is the accession BT8, and the lowest one is the accession BT1 and BM9.  Keywords: Dendogram, Leaf anatomy, Morphology, and Mango.